Penyuluhan Pencegahan Stunting di Desa Suka Mulia Kecamatan Secanggang Kabupaten Langkat - Sella Octavia; Ahmad Darlis; Habib Al Ghifari; Fitri Harabiyah Gultom; Riska Dewi; Harist Heriadi (Jurnal Pengabdian Masyarakat Nusantara, 2024)
Stunting is a chronic nutritional condition that arises from a lack of nutritional intake over a long period of time, which inhibits child growth. As a result, the child's height is below the age-appropriate standard. This condition starts during the prenatal period and continues until the child reaches the age of two. Seeing this condition, we initiated a stunting counseling program in Suka Mulia Village, Secanggang District, Langkat Regency. The purpose of this article is to present information about the implementation of stunting prevention counseling in children at the posyandu in Suka Mulia Village. The counseling was conducted through the provision of information services in collaboration with the local health office, with the aim of educating the community and encouraging them to join the stunting prevention movement. In addition, socialization programs are also conducted for residents whose children have shown stunted growth, where supplementary feeding (PMT) is provided. Therefore, this activity is an effective method to deliver information on preventing and reducing stunting in children. It is hoped that through the implementation of stunting counseling and PMT socialization in Suka Mulia Village, community awareness of child growth and development can increase, thus facilitating the prevention and reduction of stunting, and contributing to the reduction of stunting rates in Indonesia